An overview of designing an induction heating system for domestic applications - V Geetha; V Sivachidambaranathan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
The inherent benefit of the induction heating system leads to usage in the domestic applications. The design part of the coil has to be accurately manipulated to have highly qualified system. Discussion on the customisation of the coil and the converter section is elaborated such that the design relaying on the load variation, type of coil, rating required for the specified application. Thus the paper discusses about the design requirement on the domestic induction applications, depicting the criteria to be satisfied and the results are verified using the AC-AC converter fed induction heating system with the help of the equivalent circuit of the working coil and the work piece.